A Review on People’s Participation for Sustainable Rural Water Supply Systems with Special Reference to Nepal - Dahal, Khet Raj; Thapa, Narbikram; Shiwakoti, Raju (Hydro Nepal: Journal of Water, Energy and Environment, 2019)
This study was carried out during the period from March to August 2018. Published literatures and some unpublished data were collected from different sources and analyzed. It was found that the community people do not have good understanding and adequate participation on the sustainability of water supply systems. They only have interests in the regular flow in taps. They are also less aware in the regular repair and maintenance of water supply systems. Furthermore, the expectation of community is always financial support from local body and donor agency. The governance part of water user’s committee was also found unsatisfactory. Thus, the people should be provided with capacity development trainings for the sustainable development of community water supply system. similarly, implementation of water safety plan, and regular monitoring from local body are crucial activities that should be given high emphasis for the sustainability of rural water supply system.